Environmental Pollution Exposure and Its Impact on Mental and Reproductive Health: A Review - Abhinav Sahay; Arundhati Sharma; Upanshu Mishra; Badshah Alam; Rashmi Shekhar; Umesh Kumar (Journal of Psychosexual Health, 2026)
Objective: Environmental pollution is a growing global public health threat and is not limited to classic cardiopulmonary effects, impeding numerous physiological systems. Evidence of an association between environmental contaminant exposures and poor mental health, neurodevelopmental, reproductive, and pregnancy outcomes is increasing. The current evidence on main pollution sources, such as atmospheric pollution, endocrine-disrupting chemicals, heavy metals, persistent organic pollutants, pesticides, per- and polyfluorocarbons (PFAS), and emerging contaminants such as microplastics, is summarized, along with underlying biological mechanisms and public health implications. Methods: A narrative review was conducted of peer-reviewed literature, and linkages between environmental exposures and mental, reproductive, and pregnancy-related outcomes were addressed. Studies on air pollutants, bisphenols, phthalates, lead, mercury, and cadmium, pesticides, PFAS, polychlorinated biphenyls, dioxins, and microplastics were all included. The focus was on pinpointing common mechanistic features and merging together results with the exposome approach that considers exposure to the environment throughout an individual’s life. Results: When cells are continually exposed to various environmental pollutants, there is increasing evidence of these substances being linked to depression, anxiety, cognitive dysfunction, abnormalities in neurodevelopment, worsening semen quality, diminished fecundability, ovarian dysfunction, abnormalities in sexual maturation, and harmful pregnancy effects such as damage to the placenta or developmental defects in the fetus. These effects involve interrelated pathways including oxidative stress, neuroinflammation, endocrine disruption, mitochondrial dysfunction, immune dysregulation, vascular injury, and epigenetic changes. Further, it is possible that exposure to a combination of pollutants may result in additive or synergistic effects, leading to effects that are greater than would be caused by any individual pollutant, increasing vulnerability in sensitive groups such as pregnant women, infants, children, and socioeconomically disadvantaged groups. The exposome allows us to frame these exposures in a comprehensive way to understand these cumulative and lifelong exposures. Conclusion: The issue of environmental pollution severely affects mental and reproductive health and is an increasing health threat. The current evidence suggests that there is an urgent need to reinforce regulatory policies, exposure monitoring, and a surge in surveillance of health effects. Future studies should focus on longitudinal exposures, mixture exposure indicators, and using data on the exposome to understand risk and to find vulnerable human groups. There is a strong need to strengthen environmental health policies, particularly to mitigate and prevent disease burden and ensure population health in an environment with an ever-increasing disease burden and negative impacts of pollution.